2019
DOI: 10.1038/s41598-019-47559-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five glomerular filtration rate estimating equations as predictors of acute kidney injury after cardiovascular surgery

Abstract: We aimed to compare the ability of preoperative estimated glomerular filtration rate (eGFR), calculated using five different equations, to predict adverse renal outcomes after cardiovascular surgery. Cohorts of 4,125 adult patients undergoing elective cardiovascular surgery were evaluated. Preoperative eGFR was calculated using the Cockcroft-Gault, Modification of Diet in Renal Disease (MDRD) II, re-expressed MDRD II, Chronic Kidney Disease Epidemiology Collaboration, and Mayo quadratic (Mayo) equations. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…On the other hand, the GFR on hospital admission was related to the occurrence of AKI. However, even not being included in the KDIGO criteria for AKI, the GFR values are important to help in detection, understanding the severity, decision about diagnosis, prognosis and treatment of renal dysfunction ( 21 ) . Conditions such as AKI or acute CKD present with reduced baseline GFR, i.e., higher GFR values are related as a protective factor for renal function, which is in agreement with the present study ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the GFR on hospital admission was related to the occurrence of AKI. However, even not being included in the KDIGO criteria for AKI, the GFR values are important to help in detection, understanding the severity, decision about diagnosis, prognosis and treatment of renal dysfunction ( 21 ) . Conditions such as AKI or acute CKD present with reduced baseline GFR, i.e., higher GFR values are related as a protective factor for renal function, which is in agreement with the present study ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Willems et al showed that the CG and MDRD formulas effectively predicted mortality, whereas the CKD-EPI formula did not [ 20 ]. A recent study by Jo et al showed that the Mayo equation was the most accurate in predicting post-operative acute kidney injury when comparing the five eGFR formulas in 4125 adult patients undergoing elective cardiovascular surgery [ 21 ]. Fu et al showed that among 1050 patients aged > 60 years with CAD, the CKD-EPI and Mayo equations were significantly superior to the MDRD in predicting 1-year mortality, and the Mayo demonstrated mild superiority over the CKD-EPI equation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the Mayo equation was the most accurate in predicting post-operative acute kidney injury when comparing the ve eGFR formulas in 4,125 adult patients undergoing elective cardiovascular surgery (23). Fu et al showed that among 1050 patients aged >60 years with CAD, the CKD-EPI and Mayo equations were signi cantly superior to the MDRD in predicting 1-year mortality, and the Mayo demonstrated mild superiority over the CKD-EPI equation (24).…”
Section: Discussionmentioning
confidence: 99%